PENGARUH VARIABEL SOSIAL, EKONOMI, DAN DEMOGRAFIS TERHADAP KEPUTUSAN MOBILITAS ULANG-ALIK TENAGA KERJA KABUPATEN KAMPAR KE KOTA PEKANBARU - Edinur Ilham; Tri sukirno Putro; Deny Setyawan (PEKBIS, 2020)
This study aims to analyze the effect of the difference in wages, job opportunities,education level, age, marital status, number of family, and distance dependentssimultaneously, partially, and the variables that most dominantly influence thedecision to do a roundtrip migration of workers from Kampar to Pekanbaru City. Thedata used in this study are primary data obtained by conducting a direct survey tothe research area and conducting interviews based on a questionnaire that hasbeen compiled to 100 eligible respondents using a logistic regression model. Thelocation of this research is the Kampar-Pekanbaru Border (SPBU before UINSUSKA RIAU), Jalan Garuda Sakti Km 4, the main community access from TapungDistrict, Kampar Regency, Pekanbaru Pandau Trans Metro Terminal (Jl. PandauRaya) which is the main access to Pekanbaru City and Kampar Regency (Siak HuluDistrict). The independent variable in this study is the variable wages, jobopportunities, education level, age, marital status, number of family, and distancedependents, while the dependent variable is the labor decision to do round-tripmigration. The results of the study found that with a significance level of 5%, there isat least one independent variable that is statistically significant in influencing thedependent variable with an LR value of 87.11 and a p-value or prob chi2 <0.05,namely 0.0049. At the 5% significance level the variables of wages, employmentstatus, education, age, and distance in this study partially affect the migration statusvariable (roundtrip), while the marital status variable and the number of dependentsdo not affect the migration status variable (roundtrip). The wage variable is the mostdominant variable that has a significant effect on the decision variable of the returnmobility of workers from Kampar Regency to Pekanbaru City. This can be seen fromthe p-value of this variable compared to other independent variables, which is 0.041.